The utilization of junior high school mathematics national examination data: A conceptual error diagnosis - Kartianom Kartianom; Djemari Mardapi (REID (Research and Evaluation in Education), 2017)
The goal of the research is to gain insights into the characteristics of the items in the mathematics national examination, the attributes on which the items were formulated and the result of a conceptual error diagnosis of the mathematics materials based on the result of the junior high school mathematics national examination. This is quantitative descriptive research. The data were collected from 3,079 grade-nine students of junior high schools who took the National Examination in the academic year of 2015/2016. The sample was established randomly based on the package code of the examination which is P0C5520 with 574 students as the examinees. Documentation method was applied in collecting the data. The result of the research shows that – upon the implementation of the classical test theory – there are 16 items in ‘difficult’ category, 24 in ‘intermediate’ category, and no items in ‘easy’ category. Furthermore, upon the implementation of the item response theory, the result shows that 28 items are in ‘good’ category and 12 items are in ‘poor’ category. In addition, there are 50 attributes on which the Junior High School Mathematics National Examination test (package P0C520) is formulated. Four attributes are content attributes and the rest (46) are process skill attributes. The result of the diagnosis shows that there are 11 types of errors made by the students when trying to complete the content items. Most of the errors are conceptual errors related to the geometric materials especially in the sub-materials of polyhedron, triangles, and quadrangles.